Perbedaan Kejadian Gizi Lebih pada Balita Usia 1-2 tahun dengan Riwayat Pemberian Asi Eksklusif dan Bukan Asi Eksklusif di Desa Tanggul Kulon Wilayah Kerja Puskesmas Tanggul Kecamatan Tanggul Kabupaten Jember (The Difference of the Overweight Incidence t - Ely Rahmatika Nugrahani; Lantin Sulistyorini; Iis Rahmawati (Pustaka Kesehatan, 2016)
Overweight has not received much attention from caregiver. Overweight was caused by the lack of activity which was indicated by the overdeposit of fat with the value of standard deviation >+2SD. Overweight in toddlerwould caused 1,8 times overweight in adulthood. Exclusive breastfeeding was one of the ways of preventthe overweightincidence. The purpose of this research was to analyze the difference of the toddler who are given exclusive breastfeeding with the ones with nonexclusive breastfeeding regarding the overweightincidence to 1-2 years old toddler. This research used retrospectivedescriptive analysis design. The sampling collection method used in this research is total sampling, with 36 respondents involved. The results of this research reveal that 18 toddler received exclusive breastfeeding,whereas the other 18 received nonexclusive breastfeeding. The results of the statistical test reveal used Fisher Exact Test (α=0,05) and the p value = 1,000 (p value ≥ 0,05), thus the difference of the overweightincidence to 1-2 years old toodler with the exclusive and nonexclusive breastfeeding history at Tanggul Kulon under the coverage area of Tanggul Primary Health Center Tanggul Sub-District Jember Regency did not exist. Nursing of pediatriccan reduced the incidance of overweight by health education to mothers to raised awareness of importance of used exclusive breastfeeding, so the overweight does not occur. Keywords: Overweight, toddler, Exclusive Breastfeeding and Non- ExclusiveBreastfeeding